Effects of a sexual education program for people with intellectual disability - Ana Quesado; Margarida Vieira; Paula Quesado (Instituto Politécnico de Viseu, 2021)
Introduction: The person with intellectual disability is in a vulnerable situation, namely with regard to affections and sexuality. Generally, these people have precarious knowledge about sexuality, and their sexual education is insufficient or inadequate to their characteristics and needs, and it is essential for nurses to intervene in the field of sexual education with this population. The implementation of health literacy programmes aimed at people with intellectual disability, within the scope of sexuality, using inclusive strategies, can contribute to the development of healthy and safe relationships. Objetive: To assess the effects of a sex education programme on a sample of people with intellectual disabilities. Methods: Action-research developed in four cycles, between 2011 and 2015, in an institution to support people with intellectual disabilities. Results: In the first cycle, sex education was identified as a priority, and in the last one a sex education programme was implemented and its effects evaluated with the SexKen-ID scale, with improvements in the participants' knowledge being noted. Conclusion: The results of this study revealed the importance of sex education for people with intellectual disabilities and a better knowledge attainment over all the topics, when using homogeneous groups, adapted discourse and interactive strategies such as gamification. The promotion of a dynamic and reflective environment, promoted learning and experiences sharing.